Prenatal Screening and Diagnosis of ß-Thalassemia in India: Is ARMS-PCR Enough? - Ghosh, Shouriyo (Indian J Hematol Blood Transfus, 2020)
Accurate and timely prenatal diagnosis of thalassemia is cornerstone to the success of thalassemia control; currently parents are screened for ß-thalassemia mutations by ARMS-PCR and subsequently chorionic villus sampling is done. We did an audit to ascertain whether the present design is adequate and determined the role of sequencing for pre-natal diagnosis of beta-thalassemia. This was a retrospective analysis of prenatal testing data collected over 10 years, (2010–2019). ARMS-PCR was done to identify the beta-globin mutation followed by CVS wherever indicated. Data was classified into 3 groups:—5 most commonly occurring mutations (group 1), less common mutations (group 2) and mutations not detected (group 3). Total number of cases studied were 2128. Mean age of the cohort was 29.30 years (range 18–48 years). Approximately 90% individuals had one of the 5 common mutations in decreasing order of frequency: IVS 1-5 G>C (1297/2128); Codon 26G>A/HbE (451/2128); codon 30G>C (69/2128); codon 15G>A (61/2128); FS 41-42–CTTT (48/2128). Undetected mutations amounted to 7.3% (156/2128). Mean haemoglobin was highest in the group 2 (12.46 g/dl) followed by the group 1 (11.20 g/dl) and least in group 3 (10.99 g/dl). MCV, MCH and MCHC showed similar trends. ANOVA on all these parameters, except RDW, within groups and for individual mutations, were statistically significant (p < 0.001). The hemogram-HPLC-ARMS-PCR-CVS approach is a cost-effective and established method but tends to miss out a considerable number of thalassemia mutations (~7%), emphasizing the role of sequencing in difficult cases. This needs to be addressed while formulating guidelines for thalassemia screening in future.